MORPHOLOGY OF THE MAJOR SALIVARY GLANDS - Teshayeva Dilbar Shuxrat qizi (Web of Journals Publishing, 2025)
Salivary glands are crucial exocrine organs responsible for the production and secretion of saliva, which is essential for the initial stages of digestion, oral health, and antimicrobial defense. This article explores the anatomy, histology, and functional significance of the major and minor salivary glands, focusing on their cellular architecture and physiological roles in human health. Understanding the salivary glands' structure and function provides insight into various pathological conditions that can arise due to dysfunction or disease of these glands.
Keywords: Immunology, biochemistry, pH level.